Experiência do usuário e design de interação: : uma análise bibliométrica de publicações acadêmicas - Marques Paes, Vanessa; Polimeno, Claudia; Soares Souza , Cora; Priscila de Sousa Costa, Jessica; Maciel de Andrade, Renata; Gaspar, Ricardo (InfoDesign, 2022)
With advances in the digital age, terms such as user experience and interaction design have been widely used. The objective of this paper is to evaluate trends in the use of the terminologies "user experience" and "interaction design" by academic authors, analyzing the most relevant elements in the elaboration of academic articles in the areas of innovation and design. This article presents a bibliometric analysis of the terms: User Experience (UX) and Design Interaction (IXD) used in a wide range of study areas such as: Design, Artificial Intelligence and Applied Social Sciences. The term “user experience” gathers the conceptual elements that compose product-functionality and product-information, whereas “interaction design” comprises more specifically the interaction between human and product. The Bibliometrix software was used for data collection and research fulfillment. The study identifies trends in publications over the past ten years, the occurrence and relationship between keywords, the most cited publications and the countries that have used such terminology the most in academic publications